2015
DOI: 10.1002/lary.25740
|View full text |Cite
|
Sign up to set email alerts
|

Oral cavity squamous cell carcinoma metastatic to central compartment (level 6) lymph nodes

Abstract: Alterations to drainage pathways in the head and neck as a result of surgical manipulation are not well understood. We present two unusual cases of oral squamous cell carcinoma metastatic to the level 6 nodal compartment following extensive treatment. Both oral squamous cell carcinoma cases exhibited metastases to the central neck compartment following extensive surgery and radiation. Each patient had prior history of multifocal oral cavity disease and recurrent neck metastases requiring salvage lymphadenectom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…33 We identified 3 cases of recurrence in the anterior superficial lymphatic chain after IMRT for OCC, a location that is not traditionally ascribed significant risk, although treatment failures have been previously noted. 34 Consideration should be given to elective nodal coverage of this region in the postoperative setting with the use of a bolus to ensure an adequate dose superficially.…”
Section: Discussionmentioning
confidence: 99%
“…33 We identified 3 cases of recurrence in the anterior superficial lymphatic chain after IMRT for OCC, a location that is not traditionally ascribed significant risk, although treatment failures have been previously noted. 34 Consideration should be given to elective nodal coverage of this region in the postoperative setting with the use of a bolus to ensure an adequate dose superficially.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in axillary and internal mammary lymph node drainage were noted in 68% of patients. 15 An alternative hypothesis is the seeding of malignant cells in the middle aspect of the neck during previous tracheotomy as is mentioned by Likhterov et al 8 In our case, the patient did not undergo tracheostomy or any intervention in the central compartment during the previous surgery. Hence, seeding of tumor cells would not be applicable in this case.…”
Section: Discussionmentioning
confidence: 70%
“…7 Involvement of the central compartment secondary to oral squamous cell carcinoma involving the Level VI and VII neck nodes is extremely unconventional which is also ascertained by Likhterov et al in 2015 who reported two cases with central compartment involvement in recurrent oral squamous cell carcinoma for the first time in English literature. 8 We report a certainly rare case of central compartment involvement in a recurrent case of squamous cell carcinoma of tongue.…”
Section: Introductionmentioning
confidence: 89%
“…Among the five patients who developed marginal recurrence, more than a half had two clinical features in common; three patients had the primary tumor in the oral cavity and four had undergone more than two surgeries before the IMRT. In addition to the inherent resistance to radiotherapy (11,24), altered lymphovascular drainage resulting from multiple surgeries (33,34), might have contributed to the development of the marginal recurrence in these cases. Caution must be taken when delineating the CTVs in patients with these clinical features so as to reduce the risk of marginal recurrence; addition of a generous margin to CTVs might be useful.…”
Section: Discussionmentioning
confidence: 99%